(untitled) (Revista de Ciências Agroveterinárias, 2025)
Lansium domesticum, Duku, leaves contain bioactive compounds with significant health benefits, particularly as antioxidants. However, an efficient and sustainable extraction method is essential to maximize their potential. This study investigates ultrasonic-assisted green extraction (UAE) as an eco-friendly approach for optimizing the extraction of phenolic and flavonoid compounds. The optimization process involved three key parameters: solvent ratio (1:10, 1:20, 1:30, 1:40, 1:50), extraction temperature (40, 50, 60, 70, 80 °C), and extraction time (20, 40, 60, 80, 100 min), using a completely randomized design. The bioactive compound stability was assessed under various conditions, and antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH). The results demonstrated that solvent ratio and extraction temperature significantly influenced extract yield, phenolic and flavonoid content, and antioxidant activity, while extraction time affected yield and bioactive content but not antioxidant activity. The optimal extraction condition is a 1:20 powder-to-solvent ratio, 50 °C temperature, and 80 min extraction time. Yielded 5.98 ± 0.1% extract, 40.49 ± 0.9 mg AGE/g phenolic content, 185 ± 3.9 mg QE/g flavonoid content, and 38.28 ± 0.2% antioxidant activity. These findings highlight the UAE as a sustainable and effective method for extracting bioactive compounds, with promising applications in pharmaceuticals, nutraceuticals, and functional food.